The dog that did not bark: The EU and the clash between sovereignty and justice in the International Criminal Court - Costa, Oriol; Collantes-Celador, Gemma; Badell, Diego (Taylor & Francis, 2021)
The cosmopolitan character of the International Criminal Court (ICC) is not immune to the growing surge in contestation of international institutions. The African Union’s reaction to the ICC decision to indict the at the time sitting heads of state of Sudan and Kenya, and the actions undertaken by the Trump Administration against the Court over possible investigations into Afghanistan and Palestine, are cases in point. This article explores what that surge has meant for intra-EU debates on its position towards the ICC. We present a two-fold argument based on an empirical analysis of key moments in the institutional development of the Court that coincide with the pre- and post-rise phases in the politicization of international institutions. First, the level of agreement on the ICC within the EU has been grossly exaggerated. Second, despite bouts of disagreement, patterns of political conflict over the ICC within the EU remain constant. That is, there is recurrent polarization, with a range of opinions on the intractable debate of Westphalian sovereignty vs. cosmopolitan justice, but no change in the other two dimensions of politicization (salience and actor range).
Keywords: International Criminal Court; European Union; Contestation